Геопросторовий аналіз антропогенних змін ландшафтно-геохімічних умов території (теоретичний аспект) - Сорокіна, Л.Ю.; Рога, І.В. (Український географічний журнал, 2011)
Проанализированы теоретические положения и базовые понятия исследования ландшафтно-геохимических условий территории. Отмечено, что ландшафтно-геохимические условия территории определяют геохимическую структуру антропогенно измененных ландшафтных комплексов и характер миграци химических элементов. Сформулировано понятие геохимического урочища как промежуточной единицы в иерархии ландшафтно-геохимических территори-альных единиц. Антропогенные воздействия рассматриваются как фактор изменения геохимических параметров ландшафтно-геохимических систем. Подчерктнуто значение ландшафтоведчексо-геохимических исследований для геоэкологических оценок современных антропогенно измененных ландшафтов. The theoretical principles and basic conceptions of research of anthropogenic changes of landscape-geochemical conditions of a territory are considered. Landscape-geochemical conditions determine geochemical structure of anthropogenically changed landscapes and the characteristics of chemical elements migration. It is substantiated the conception of “geochemical urochishche” as an intermediate unit in the hierarchy of landscape-geochemical territorial units. Anthropogenic changes are considered as a factor of changes of geochemical parameters of landscape-geochemical systems. It is emphasized the importance of landscape-geochemical research for geoecological assessments of modern anthropogenically changed landscapes.